A predictive model for residual disease after (chemo) radiotherapy in oropharyngeal carcinoma: Combined radiological and clinical evaluation of tumor response. (October 2017) - Gouw, Zeno A.R.; Jasperse, Bas; Sonke, Jan-Jakob; Heemsbergen, Wilma D.; Navran, Arash; Hamming-Vrieze, Olga; Paul de Boer, Jan; van den Brekel, Michiel W.M.; Al-Mamgani, Abrahim
Abstract: Background and purpose: Early detection of Residual disease (RD) is vital for salvage possibilities after (chemo) radiatiotherapy for oropharyngeal carcinoma (OPC). We standardized clinical investigation to test its added value to MRI response evaluation and investigated the benefit of FDG-PET/CT. Materials and methods: Radiological response evaluation using Ojiri-score was done for 234 patients with OPC, using MRI 12 weeks after (chemo) radiotherapy between 2010 and 2014. The presence of mucosal lesions and/or major complaints (still completely tube feeding-dependent and/or opiate-dependent because of swallowing problems) was scored as clinical suspicion (CS). Retrospectively, the performance of Ojiri to predict RD was compared to CS and both combined using Pearson Chi-squared. Of the whole group, FDG-PET/CT metabolic response (MR) was available in 50 patients. Results: Twelve out of 234 patients (5.1%) had RD. Ojiri and CS had excellent negative predictive value (NPV) (98% and 100% respectively). The combination of CS and Ojiri reduced false positives by 32% (38–26 patients) without lowering NPV (98%). No patients with complete MR ( n = 39) at the FDG-PET/CT had RD compared to 5 (45%) with partial MR. Conclusion: For response evaluation in OPC, the combination of CS and Ojiri-score improved the predictive accuracy by reducing false positives compared to them individually. FDG-PET/CT is promising to further reduce false positives.